Preliminary Experimental Study of Methane Adsorption Capacity in Shale After Brittle Deformation Under Uniaxial Compression - Liang, Mingliang; Wang, Zongxiu; Zheng, Guodong; Zhang, Xiaobao; Greenwell, Hugh Christopher; Zhang, Kaixun; Feng, Xingqiang; Zhang, Linyan; Li, Huijun (Frontiers in Earth Science, 2021)
This paper presents an preliminary experimental study on the change of methane adsorption capacity in shales after artificial deformation. The experimental results are based on uniaxial compression and methane isothermal adsorption tests on different shale samples from the Silurian Longmaxi Formation, Daozhen County, South China. Two sets of similar cylindrical samples were drilled from the each same bulk sample, one set was subjected to a uniaxial compressive simulation test and then crushed as artificial deformed shale sample, the other set was directly crushed as the original undeformed shale sample. And then we conducted a comparative experimental study of the methane adsorption capacity of original undeformed and artificially deformed shales. The uniaxial compression simulation results show that the failure mode of all samples displayed brittle deformation. The methane isothermal adsorption results show that the organic matter content is the main controlling factor of shale methane adsorption capacity. However, the comparative results also show that the compression and deformation have an effect on methane adsorption capacity, with shale methane adsorption capacity decresasing by about 4.26-8.48% after uniaxial compression deformation for the all shale samples in this study.